The Readiness of Lecturers in Online Learning During the Covid-19 Pandemic at the Faculty of Information Technology and the Faculty of Economics and Business - M.J. Dewiyani Sunarto (IJORER : International Journal of Recent Educational Research, 2021)
This research aims to determine the readiness of lecturers in implementing online learning on both faculties at a University in Surabaya during the first semester of the pandemic, especially in terms of (1) the use of synchronous learning mode, (2) the use asynchronous learning mode with e-learning, (3) the strengths and weaknesses of online learning that have been implemented by lecturers. This research was conducted on 126 lecturers in both faculties with a total of 350 classes. The research instrument used an electronic log from the campus e-learning application, and was analyzed using a descriptive method. The results showed that (1) the use of synchronous learning mode was used by 72% and 64% of the total amount of learning performed at the Faculty of Information Technology and at the Faculty of Business Economics, respectively (2) the use of campus e-learning as the media for asynchronous learning for delivering materials by 94% and 50.01% (3). The strength of online learning for lecturers is the availability of supporting applications and teaching materials which can be used by learners, while the weakness is on the understanding of online philosophy. From the results of this research, it is recommended to increase the readiness of lecturers to perform online learning, in the form of understanding the online philosophy, and institutional support to provide interesting contents for online learning, so it can be carried out in accordance with its philosophy, as asset for future online learning, even though if there will be no Covid-19 Pandemic.